2008
DOI: 10.1172/jci34193
|View full text |Cite
|
Sign up to set email alerts
|

HOXA11 is critical for development and maintenance of uterosacral ligaments and deficient in pelvic prolapse

Abstract: Pelvic organ prolapse (POP) is a common, debilitating disorder affecting millions of women. Uterosacral ligaments (USLs) are the main supportive structures of the uterus and vagina and are often attenuated in women with POP. Although the mechanical strength of USLs is known to be dependent on collagen synthesis and catabolism and the degradation protein MMP2 has been implicated in POP, the molecular mechanisms involved in the development of POP are currently unknown. Homeobox (HOX) genes are transcriptional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 30 publications
2
48
0
4
Order By: Relevance
“…Interestingly, these proteins are abundantly expressed in the vaginal wall and involved in synthesis and assembly of elastic fibers. It is also known that uterosacral ligaments support the vaginal wall and that Hoxa11 is essential for formation of uterosacral ligaments in mice (9). Hoxa11-deficient mice exhibit increased mobility of the uterus; however, POP was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these proteins are abundantly expressed in the vaginal wall and involved in synthesis and assembly of elastic fibers. It is also known that uterosacral ligaments support the vaginal wall and that Hoxa11 is essential for formation of uterosacral ligaments in mice (9). Hoxa11-deficient mice exhibit increased mobility of the uterus; however, POP was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen metabolism is largely regulated by matrix metalloproteinases (MMPs), which are zinc-dependent endopeptidases that degrade collagen; over 20 different MMPs have been identified [9]. Multiple studies have revealed higher MMP activity in patients with SUI and POP as compared to control patients [6,[10][11][12][13]. With increasingly more information available regarding the etiologies of pelvic floor dysfunction, there is a need for treatment strategies to incorporate this knowledge and translate it into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous and homozygous Hoxa11-deficient mice have malformations in the lower and hind limbs, consistent with the observations in patients, but thrombocytopenia has never been reported. 73,74 At present, it is not known whether the megakaryocytopoietic defects present in patients result from a dominant negative effect of the point mutations or not. 75 …”
Section: Radioulnar Synostosis With Amegakaryocytosis Thrombocytopenimentioning
confidence: 99%